Contribución de los recursos didáctico tecnológicos en el desarrollo cognitivo de los estudiantes del octavo, noveno y décimo año de educación básica, paralelo A del centro educativo Profesores Sara Serrano de Maridueña de la parroquia de Puerto Bolívar de la ciudad de Machala del periodo académico 2013 - 2014. - Chillambo Chávez, Karen Viviana (2014)
The research falls within a line of technological support to teachers . Its primary purpose appropriate to settle the technological educational resources aimed at teachers of basic education strategies. By virtue of the results obtained and the dissatisfaction of information, it became clear that the teaching strategies used by most teachers is exposure . Therefore , it states that the use of appropriate teaching strategies in technology supported learning resources argues the proposal to the school participating in the investigation.